Quality Evaluation of Household Wastewater for Irrigation - JJ Musa; OG Ode; SC Anijofor; JK Adewumi (Journal of Applied Sciences and Environmental Management)
Water is becoming an increasingly scarce resource and planners are forced to consider any sources of water which might be used economically and effectively to promote further development. Irrigated agriculture occupies approximately 17 percent of the world’s total food production. Whenever good quality water is scarce, water of marginal quality will have to be considered for use in agriculture. Domestic wastewater varies in composition from place to place due to different water sources used and also the composition and soil minerals from these sources. Ten samples were collected respectively from kitchen, laundry and toilet wastewaters were collected and physical, chemical, metallic and non-metallic analysis were carried out on the various samples collected following standard procedures. @JASEM